Individual variability of dewlap and antlers of the European elk Alces alces (L., 1758) on the territory of the Leningrad Province (Russia) according to observations with camera traps mounted nearby artificial salt licks - Nickolay V. Sedikhin (Трансформация экосистем, 2022)
Visually identifiable morphological features serve as distinctive signs of individuals and may indicate the state and sexage structure of populations of large mammals. The development and change of morphological structures may occur under the influence of various factors, including human economic activity. The article proposes a classification of dewlap and antler morphotypes of the population of the European elk (Alces alces alces (L., 1758)), living on the territory of the Leningrad Province (North-West of Russia). Frequency of occurrence of observed morphotypes is analyzed and discussed considering the data of long-term observations conducted in 2015–2020 at 20 artificial salt licks located on 11 experimental sites in three districts of the region. Based on the studied material, the following morphotypes of the dewlap are identified: “icicle”, “drop”, and “fold” (halberd, triangular, rounded). In females, the dewlaps of the “icicle” and “drop” type dominate, the “fold” is noted very rarely. In males, on the contrary, the “fold” is most often encountered. The antlers may be palmated, cervine, intermediate, transitional, “spike”, “fork”, and abnormal. Palmate and cervine antlers are found with almost the same frequency of occurrence (about 25%), a lower number of cases is noted for “spikes” and “forks”, as well as for intermediate type of antlers; transitional and abnormal antlers are recorded the least. The analysis of literary sources devoted to the classification and variability of the studied morphological characters has been also carried out.